1978
DOI: 10.1021/i160066a006
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Breakage and Coalescence Processes in an Agitated Dispersion. 2. Measurement and Interpretation of Mixing Experiments

Abstract: Simultaneous measurements of the drop size distributions and rate of dispersed-phase mixing were obtained for an agitated liquid-liquid dispersion in a 1.36-L vessel under steady-state, continuous flow conditions. The impeller speed was varied from 160 to 278 rpm, and the dispersed phase fraction from 0.05 to 0.20. A regime was discovered in which the rate of dispersed-phase mixing varied as the impeller speed to about the tenth power, while the mean drop size was little altered. This is interpreted as a compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Therefore, these values are considered universal and will be kept unchanged throughout this investigation. However, the value of these constants were found to be several orders of magnitude larger than those obtained by previous authors who used the same model to simulate liquid-liquid dispersions using MATs [50,[54][55][56][57]. The discrepancy depicted in Table 5 is most probably due to the simplifying assumptions used by these authors in which they assumed a uniform local energy dissipation rate throughout the entire volume of the MAT.…”
Section: Matching Model Predictions With Experimental Datamentioning
confidence: 69%
“…Therefore, these values are considered universal and will be kept unchanged throughout this investigation. However, the value of these constants were found to be several orders of magnitude larger than those obtained by previous authors who used the same model to simulate liquid-liquid dispersions using MATs [50,[54][55][56][57]. The discrepancy depicted in Table 5 is most probably due to the simplifying assumptions used by these authors in which they assumed a uniform local energy dissipation rate throughout the entire volume of the MAT.…”
Section: Matching Model Predictions With Experimental Datamentioning
confidence: 69%
“…The appropriate valué of m can only be determined if experimental data is available. Hsia and Tavlarides (1983) found that the truncated normal model proposed by Coulaloglou and Tavlarides (1977) was unable to predict the results obtained by Ross (1971), Verhoff et al (1977), and Ross et al (1978). Consequently, they modified the earlier work, assuming binary break-up and a beta distribution, rather than the truncated normal distribution.…”
Section: Statistical Modelsmentioning
confidence: 94%
“…Similarly, measurement of bubble sizes in turbulent flows does not provide information on the independent contributions of break-up and coalescence rates, both of which determine bubble size. While various models consider these rate processes independently for the case of liquid-liquid systems (Coulaloglou and Tavlarides, 1977;Ross et al, 1978; Valentas and Amundson, 1966), these models have not been tested due to a lack of experimental data on the individual rate processes. There are also differences in behavior between liquid-liquid and gas-liquid systems which must be considered in modeling bubble coalescence and break-UP.…”
mentioning
confidence: 99%